أثر المدخل الاتصالي في تعلم اللغة العربية للناطقين بغيرها في معاهد تأهيل المعلمين - Sani, Aliyu Muhammad (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2024)
This research aims to explore the impact of the communicative approach on teaching Arabic in teacher training institutes using an experimental method. An assessment was used as a research tool, including grammatical and social competence tests. The researcher ensured the tool's validity by presenting it to specialized judges and verifying its reliability by analyzing test results. The sample included 55 Arabic language students, who were selected purposefully, with 30 representing the experimental group and 25 representing the control group. After administering the test, the results were collected and analyzed using statistical methods, including percentage frequencies, arithmetic mean, standard deviation, and T-tests to measure differences between the two groups. The results showed statistically significant differences between students' average scores in the two groups in the grammatical and social competence tests. Based on these findings, the researcher recommended training Arabic language teachers to apply the communicative approach through practical training and follow-up and attending workshops and seminars to develop their performance in applied linguistics with a focus on the communicative approach. The researcher also recommended raising awareness among education students about the importance of the communicative approach and encouraging them to use it in the future as teachers.